Palmitic acid-rich diet suppresses glucose-stimulated insulin secretion (GSIS) and induces endoplasmic reticulum (ER) stress in pancreatic islets in mice. (2nd January 2016) - Hirata, Takumi; Kawai, Toshihide; Hirose, Hiroshi; Tanaka, Kumiko; Kurosawa, Hideaki; Fujii, Chikako; Fujita, Haruhisa; Seto, Yoshiko; Matsumoto, Hideo; Itoh, Hiroshi
Abstract: The objective was to clarify whether dietary palmitic acid supplementation affects glucose-stimulated insulin secretion (GSIS) and the endoplasmic reticulum (ER) stress pathway in pancreatic islets in mice. Eight-week-old male C57BL/6J mice were randomly divided into three treatment diet groups: control diet, palmitic acid-supplemented diet (PAL) and oleic acid-supplemented diet (OLE). After 2 weeks of treatment, intraperitoneal glucose tolerance test and intraperitoneal insulin tolerance test were performed. GSIS was assessed by pancreatic perfusion in situ with basal (100 mg/dL) glucose followed by a high (300 mg/dL) glucose concentration. We measured mRNA levels of ER stress markers such as C/EBP homologous protein (CHOP), immunoglobulin heavy-chain binding protein (BIP) and X-box binding protein (XBP)-1 using real-time polymerase chain reaction (PCR) analyses in isolated islets. Immunohistochemical staining was also performed. Mice fed PAL showed significantly decreased glucose tolerance ( p < 0.05). In the perfusion study, GSIS was significantly suppressed in the PAL group ( p < 0.05). Semi-quantitative RT-PCR revealed that islet CHOP, BIP, and XBP-1 mRNA expression were significantly increased in the PAL group ( p < 0.05). TUNEL-positive β-cells were not detected in all groups. Dietary palmitic acid-supplementation for 2 weeks might suppress GSIS and induce ER stress in pancreatic islets in mice, in the early stage of lipotoxicity.